The problem of the legal status of artificial intelligence in Algerian legislation - Hassaine Oumria (Journal of Science and Knowledge Horizons, 2025)
This intervention addresses the rapid advancements in science and industry, particularly in artificial intelligence (AI). Unlike traditional programs, AI systems operate autonomously and make unpredictable decisions based on their environment, raising concerns about responsibility for their actions. The widespread use of AI and robots presents significant challenges, especially regarding accountability and the adequacy of existing legislation.Accordingly, this study examines current and future challenges of AI, with a focus on its legal regulation under Algerian law. It explores the legal status and potential legal personality of AI to determine liability for errors it may cause. Given the growing prevalence of AI and the likelihood of related crimes, legislative intervention is essential to address its legal recognition and consequences.